2021
DOI: 10.1002/adfm.202107139
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Grafted Nanoparticles as Single‐Component, High Filler Content Composites via Simple Transformative Aging

Abstract: Polymer‐grafted nanoparticles (PGNPs) are ideal additives to enhance the mechanical properties and functionality of a polymer matrix and can even potentially serve as single‐component building blocks for highly filled composites if the polymer content is kept low. The major challenge facing such syntheses is that PGNP‐based solids with short polymer brushes often have low mechanical strength and limited processability. It therefore remains difficult to form robust architectures with a variety of 3D macroscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Previous work on the thermal aging of methacrylate PGNPs has shown that heating these polymers in air can cause the formation of anhydride cross-links between polymer chains and a loss of organic content due to the chemical transformation. 26 This thermal aging therefore transforms the "green" composite into a rigid and highly filled PMNC (>40 vol % filler). The major challenges for using such a method to generate functional composites with improved conductivity therefore lie in the development of chemistries to incorporate more thermally conductive fillers (without negatively affecting the cross-linking reaction) and in characterizing how these high filler content, non-percolating composites with large amounts of organic inorganic interface and covalent networks affect thermal transport.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work on the thermal aging of methacrylate PGNPs has shown that heating these polymers in air can cause the formation of anhydride cross-links between polymer chains and a loss of organic content due to the chemical transformation. 26 This thermal aging therefore transforms the "green" composite into a rigid and highly filled PMNC (>40 vol % filler). The major challenges for using such a method to generate functional composites with improved conductivity therefore lie in the development of chemistries to incorporate more thermally conductive fillers (without negatively affecting the cross-linking reaction) and in characterizing how these high filler content, non-percolating composites with large amounts of organic inorganic interface and covalent networks affect thermal transport.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previous work on the thermal aging of methacrylate PGNPs has shown that heating these polymers in air can cause the formation of anhydride cross-links between polymer chains and a loss of organic content due to the chemical transformation . This thermal aging therefore transforms the “green” composite into a rigid and highly filled PMNC (>40 vol % filler).…”
Section: Resultsmentioning
confidence: 99%
“…On the 1st HL, the organic functionalization of the inorganic cores allows for further adjustment of the SC properties. Different suitable possibilities have been developed [12][13][14][15][16][17][18][19][21][22][23][24][25] to tailor the interparticle cohesion. Herein, NC-interfacing organic ligands were crosslinked before embedding the SPs into the epoxy matrix via an annealing step under inert atmo-sphere, which substantially increases the robustness of the SC-materials.…”
Section: Resultsmentioning
confidence: 99%
“…4 Creating strong connections between single NCs has therefore started to gain increasing attention and, as such, remarkable steps forward have been made by connecting polymer-grafted NCs via hydrogen-bonding, [12][13][14][15][16][17] metal coordination, [18][19][20] or crosslinkable chemical moieties. [21][22][23][24][25] However, the large molecular weights of the surface grafted polymers result in a high content of soft organic phases in the final bulk materials, limiting their overall mechanical properties to values in the range of neat polymers (typical elastic moduli below 2 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…
matrix, [4,5] the interface between the matrix and the filler, [6,7] and particularly by the filler properties, including the orientation, agglomeration state, and network state. [8][9][10][11][12] The thermal conductivity of polymer composites can be increased by changing the orientation and aggregation state of the filler material to increase the length of the mean free path of phonons. [13,14] In addition, the formation of a percolation network, which facilitates long-range connectivity in a random system of fillers, is crucial for lengthening the mean free path of phonons.
…”
mentioning
confidence: 99%